Hubungan Pengetahuan dan Pelaksanaan End Of Life Care Pada Masa Pandemi Covid-19 - Muthia, Rahmi; Fitri, Tiya Rama; Mailani, Fitri; Oktarina, Elvi; Huriani, Emil (Universitas Fort De Kock Bukittinggi, 2023)
Background: During the Covid 19 pandemic, the need of care and the death rate of patients in the Intensive Care Unit (ICU) increased. So that nurses are required to to integrate the implementation of end of life care (EOLC) in end of life (EOL) patients. However, the implementation of EOLC during the Covid 19 pandemic was vulnerable to obstacles. The implementation of EOLC treatment is influenced by knowledge. The purpose of this study was to see the relationship between knowledge and implementation of EOLC during the COVID-19 pandemic in the Intensive Care Unit room. Methods: This research is a descriptive correlation with a cross sectional approach. The research sample was 91 people, using a convenience sampling technique. This research was conducted in August-October 2022 with research respondents in intensive care nurses at the Hospital in Padang City who worked during the Covid 19 pandemic for at least 1 year. Data collection used Palliative Care Quiz for Nurse Indonesian Version (PCQN-I) and Self Reported Practice Checklist. Data analysis used fisher's exact test. Results: The results showed that nurses' EOLC knowledge was in the moderate category (82.4%) and the implementation of end of life care by nurses during the Covid 19 pandemic was in the high category (85.7%). Conclusion: There was no relationship between EOLC knowledge and EOLC implementation during the Covid 19 pandemic (p = 0.451). Hospital institutions are advised to facilitate the increase of end of life care knowledge in nurses so as to support optimal implementation. Keywords: End of Life Care, Knowledge, Implementation, Nurse, Intensive Care Unit